Difficulties In Translating Metaphorical And Symbolic Elements In Narratives About Amir Timur (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the key difficulties involved in translating metaphorical and symbolic elements in narratives depicting Amir Timur across English and Russian literary traditions. The study focuses on how culturally embedded metaphors, historical symbolism, and ideologically shaped imagery challenge the achievement of semantic equivalence in translation. Using a comparative literary and discourse-analytical approach, the research analyzes selected texts from both traditions to identify recurring translation problems, including loss of connotation, distortion of symbolic meaning, and shifts in evaluative tone. Special attention is given to the role of cultural context, intertextual references, and translator subjectivity in shaping the reconstructed image of Timur. The findings demonstrate that metaphor and symbolism are not merely linguistic features but carriers of cultural memory and ideological framing. The article proposes context-sensitive translation strategies that preserve both meaning and stylistic nuance in cross-cultural narratives.